Karakteristik Genetik Eksternal Ayam Kampung di Kecamatan Sungai Pagu Kabupaten Solok Selatan - Subekti, Kusnadidi; Arlina, Firda (Fakultas Peternakan Universitas Jambi, 2011)
The purpose of this research is to determine external genetic characteristic that contents cualitatif and cuantitatif traits native chicken at Sungai Pagu Solok Selatan region. This reseachs using 150 native chicken which is 50 male and 100 female in mature period. Reseachs method by survey and sampling method using multi stage random sampling. Data analized by statistic descriptive. Results of this research showed that feather color of male is wild feather type 38%, gold 22%, black 14%, white 10%, bar 10%, and columbian 6%. Single comb pattern 44%, rose 32%, pea 16%, and walnut 4%. Legs color skin(shank) yellow/white 74% and black 26%. Feather color at female is black 50%, bar 17%, gold 12%, white 10%, wild feather type 5%, columbian 4% and white silver(S) 2%. Pea comb pattern 48%, walnut 25%, single 21%, rose 6%. Legs color skin yellow/white 66% and black 34%. The male length of tarsometatarsus was 103.60 mm, tibia 144.48 mm, femur 109.24 mm, comb height 23.15 mm, body weight 1.90 kg, wing length 218.41 mm, length of third legs toe 73.20 mm. While, on the female has length of tarsometatarsus 81.07 mm, tibia 125.34 mm, femur 95.39 mm, comb height 9.89 mm, body weight 1.36 kg, measures of os pubic 30.06 mm, wing length 188.65 mm, and length of third legs toe were 63.52 mm.